Comparison of vitamin D (25OHD) status between fertile and infertile men - Nasreen, Khaleda; Ishrat, Shakeela; Banu, Jesmine; Fatima, Parveen; Ansary, Selina Afroz; Jahan, Israt; Afrin, Shajia; Karim, M. Rezaul; Islam, M. Kamrul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vitamin D (25OHD) deficiency has become a modern-day epidemic, being the most common nutritional deficiency worldwide. Many infertile men are experiencing low total sperm count or different semen abnormalities. The aim of this study was to compare serum vitamin D (25OHD) status among fertile and infertile men. Methods: This was an observational (cross sectional comparative) study and was conducted in the Department of Reproductive Endocrinology and Infertility, BSMMU, Dhaka, Bangladesh during the period from April 2019 to March 2020. The sample size was 112 men where 56 participants were in fertile men group and 56 participants were infertile men group. Statistical analyses were carried out by using Windows based Statistical Package for Social Sciences (SPSS, version 23.0). Results: The predictability of vitamin D insufficiency was significant. Holding the effects of vitamin D deficiency constant, males with vitamin D insufficiency were 3.28 times more likely to be infertile than males with vitamin D sufficiency. Subgroup analysis of infertile men was done regarding semen parameters in different vitamin D status categories. There was statistically significant difference in semen volume and sperm concentration between infertile men of different vitamin D status but no significant difference in case of motility and morphology. Conclusions: There was no significant different of serum vitamin D (25OHD) between fertile and infertile men. Men with vitamin D insufficiency (≥20 ng/ml to <30 ng/ml) are more likely to be infertile than men with vitamin D sufficiency.